2014
DOI: 10.3846/16111699.2012.729155
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intellectual Capital of Lithuanian Cities by a Composite Index

Abstract: The article comprises analysis of theoretical and practical aspects of measurement of the city's intellectual capital. This article includes analysis of the intellectual capital concept and possibilities of its application at the city level, generalization of the organization intellectual capital models and principles, which, considering the macro-level context and overview of tendencies of economic growth, are applied for measurement of intellectual capital of the city. The newly created city's intellectual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…IC research at "macro" and "meso" levels has been gaining some importance in the past decade. Nevertheless, a lack of academic discussion about IC at these levels still subsists (Krušinskas and Bruneckienė, 2015). Most IC research at higher levels of analysis has been focused on Nations, namely, as a means to support decision making with the aim of increasing wealth (Seleim and Bontis, 2013;Labra and Sánchez, 2013).…”
Section: Ic Beyond Individual Organizationsmentioning
confidence: 99%
“…IC research at "macro" and "meso" levels has been gaining some importance in the past decade. Nevertheless, a lack of academic discussion about IC at these levels still subsists (Krušinskas and Bruneckienė, 2015). Most IC research at higher levels of analysis has been focused on Nations, namely, as a means to support decision making with the aim of increasing wealth (Seleim and Bontis, 2013;Labra and Sánchez, 2013).…”
Section: Ic Beyond Individual Organizationsmentioning
confidence: 99%
“…The analysis revealed that application of econometric and non-econometric -qualitative methods offers opportunities to describe the competitive position of cities or regions and envisage their future perspectives more explicitly and comprehensively. In their other articles (Bruneckiene, Krusinskas, 2011, Bruneckiene et al, 2010, Snieska, Bruneckiene, 2009) the authors of this article provided a comprehensive presentation on peculiarities, advantages and disadvantages of measuring urban and regional competitiveness by index; also they provided justification on suitability of this method for measuring territorial competitiveness.…”
Section: Diversity Of Methods On Measuring Urban Competitivenessmentioning
confidence: 99%
“…The most important component of RIC is human capital, which is generally accepted by scholars [4,9,10,18,[43][44][45][46][47][48][49][50][51]. Measuring and evaluating knowledge in human capital is a very important and interesting area [52].…”
Section: Literature Review 21 Components Of Intellectual Capitalmentioning
confidence: 99%